Examining the Association Between Trauma Characteristics and Adult Depression and Anxiety: Analysis of Types, Variety, Repetition, and Timing of Past Trauma - Hong, Sunghyun H.; Yu, Chi-Lin; Rousson, Ashley N.; Bender, Anna E.; Fedina, Lisa; Herrenkohl, Todd I. (Journal of interpersonal violence, 2024)
Past research has emphasized the impact of prior trauma on adult depression and anxiety rates. However, few studies have examined the simultaneous connection between various trauma characteristics (e.g., type, variety, repetition, timing) and symptoms of depression and anxiety in adults. Understanding how these different trauma characteristics relate to mental health issues can offer valuable insight into predicting the onset of such problems. We conducted a cross-sectional analysis with 356 adult participants to explore the associations between lifetime trauma history and depression/anxiety scores. Participants retrospectively reported on five different traumatic experiences from birth to the present, including childhood physical abuse, witnessing parental violence, lifetime experiences of rape, witnessing trauma to loved ones, and the unexpected death of loved ones. For each trauma type, participants indicated the timing of their first exposure and the frequency of subsequent occurrences. Depression and anxiety symptoms in the past 2 weeks were also self-reported. Multiple regression analyses with covariates were employed. On average, participants experienced two out of the five trauma types. Regardless of the type, having at least one traumatic experience was linked to higher depression and anxiety scores. Those who experienced all five trauma types reported the highest levels of depression and anxiety. Repeated instances of rape, witnessing trauma to loved ones, and the death of loved ones were significantly associated with elevated depression and anxiety scores. The timing of exposure to the unexpected death of loved ones predicted higher depression scores in childhood compared to adulthood, while no relationship between timing and anxiety scores was observed. Other trauma types did not show significant associations. Our study enhances knowledge of the link between trauma and depression/anxiety by elucidating how various trauma characteristics, such as type, variety, repetition, and timing of trauma, have differential influences on depression and anxiety scores.